2023
DOI: 10.1136/bmjopen-2022-070832
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intensive lipid lowering compared with moderate-intensity lipid lowering on coronary atherosclerotic plaque phenotype and major adverse cardiovascular events in adults with low to intermediate 10-year ASCVD risk (ILLUMINATION study): protocol for a multicentre, open-label, blinded-endpoint, randomised controlled trial

Abstract: Introduction Current guidelines recommend moderate-intensity lipid lowering (low-density lipoprotein cholesterol, LDL-C of <2.6 mmol/L or 30%–49% reduction from the baseline) for patients with intermediate 10-year atherosclerotic cardiovascular disease (ASCVD) risk. The effects of intensive lipid lowering (LDL-C of <1.8 mmol/L) on coronary ath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Prevention of cerebrovascular disease is important in clinical practice, and lipid-lowering drugs are currently commonly used [ 10 , 11 ]. Studies have shown a reduction in the occurrence of ASCVD via a decrease in LDL-C levels [ 12 , 13 ]. Several studies have further recommended reducing LDL-C levels to very low levels [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prevention of cerebrovascular disease is important in clinical practice, and lipid-lowering drugs are currently commonly used [ 10 , 11 ]. Studies have shown a reduction in the occurrence of ASCVD via a decrease in LDL-C levels [ 12 , 13 ]. Several studies have further recommended reducing LDL-C levels to very low levels [ 14 ].…”
Section: Introductionmentioning
confidence: 99%